A wideband reflectarray antenna based on organic substrate materials - H. I. Malik; M. Y. Ismail; Sharmiza Adnan; S. R. Masrol; N. Nafarizal (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Significant improvements in terms of bandwidth of reflectarray antennas have been achieved by introduction of innovative paper substrate dielectric materials. Three differently custom composed organic dielectric substrates have been characterized for dielectric properties using a broadband technique based on open ended coax cable method. The substrates show low dielectric permittivities of 1.81, 1.63 and 1.84 along with a loss tangent of 0.053, 0.047 and 0.057. Validation of using the proposed substrates for reflectarray antenna was done by modelling and fabricating reflectarray unit elements on the three substrates. Scattering parameter analysis of unit reflectarray elements show encouraging results with a broadband frequency response of 340 MHz at a phase gradient of 0.14 º/MHz. Thus the proposed substrate could serve exceptionally to address the narrow bandwidth problem in reflectarray antennas.